An assessment of the functional outcomes of patients undergoing early exercise physiotherapy following arthroscopic rotator cuff repair using the double-row suture bridge technique - Dias, Nixon K.; Sera, Rakesh (International Journal of Research in Orthopaedics, 2020)
Background: The methods of repairing rotator cuff tear are single-row technique, traditional double-row technique and suture-bridge technique. Studies have shown that the arthroscopic suture-bridge technique improved the pressurized contact area between the tendon and footprint. Controversy exists regarding the influence of early versus delayed motion on stiffness and healing rate after cuff repair. Early motion rehabilitation increases range of motion after cuff repair, although risk of re-tear is higher compared to immobilization. This study evaluated the functional outcomes in patients who underwent arthroscopic rotator cuff repair using the suture-bridge technique followed by an early exercise physiotherapy regime. Methods: The study was a prospective and retrospective analysis of patients treated arthroscopically for rotator cuff tears in Hosmat hospital, Bangalore. 30 patients who had only a supraspinatus/infraspinatus tear were included in the study. The functional outcome was assessed by two scoring systems, UCLA and ASES scores. Post operatively, patients were immobilized for 3 weeks only. They were followed up at 3 weeks, 6 weeks, 12 weeks and at 6 months. Results: Our study had 20 patients reporting a good outcome, whereas 9 patients had a fair outcome. Only 1 patient reported a poor outcome. The mean ASES scores improved from 20.43 to 77.87 whereas the UCLA score improved from 10.03 to 27.93. None had re-tears. Conclusions: The arthroscopic suture-bridge technique resulted in acceptable patient satisfaction and functional outcome as 67% of our patients had a “good” outcome. Early ROM exercise accelerated recovery from postoperative stiffness for patients after arthroscopic rotator cuff repair.